Ruminal background of predisposed milk urea (MU) concentration in Holsteins - Honerlagen, Hanne; Reyer, Henry; Segelke, Dierck; Müller, Carolin Beatrix Maria; Prahl, Marie Christin; Ponsuksili, Siriluck; Trakooljul, Nares; Reinsch, Norbert; Kuhla, Björn; Wimmers, Klaus (Frontiers in Microbiology, 2022)
Efforts to reduce nitrogen (N) emissions are currently based on the optimization of dietary- N supply at average herd N requirements. The implementation of the considerable individual differences and predispositions in N- use efficiency and N- excretion in breeding programs is hampered by the difficulty of data collection. Cow individual milk urea (MU) concentration has been proposed as an easy-to-measure surrogate trait, but recent studies questioned its predictive power. Therefore, a deeper understanding of the biological mechanisms underlying predisposed higher (HMUg) or lower (LMUg) MU concentration in dairy cows is needed. Considering the complex N- metabolism in ruminants, the distinction between HMUg and LMUg could be based on differences in (i) the rumen microbial community, (ii) the host-specific transcription processes in the rumen villi, and (iii) the host–microbe interaction in the rumen. Therefore, rumen fluid and rumen epithelial samples from 10 HMUg and 10 LMUg cows were analyzed by 16S sequencing and HiSeq sequencing. In addition, the effect of dietary-N reduction on ruminal shifts was investigated in a second step. In total, 10 differentially abundant genera (DAG) were identified between HMUg and LMUg cows, elucidating greater abundances of ureolytic Succinivibrionaceae_UCG-002 and Ruminococcaceae_unclassified in LMUg animals and enhanced occurrences of Butyvibrio in HMUg cows. Differential expression analysis revealed genes of the bovine Major Histocompatibility Complex (BOLA genes) as well as MX1, ISG15, and PRSS2 displaying candidates of MU predisposition that further attributed to enhanced immune system activities in LMUg cows. A number of significant correlations between microbial genera and host transcript abundances were uncovered, including strikingly positive correlations of BOLA-DRA transcripts with Roseburia and Lachnospiraceae family abundances that might constitute particularly prominent microbial–host interplays of MU predisposition. The reduction of feed-N was followed by 18 DAG in HMUg and 19 DAG in LMUg, depicting pronounced interest on Shuttleworthia, which displayed controversial adaption in HMUg and LMUg cows. Lowering feed-N further elicited massive downregulation of immune response and energy metabolism pathways in LMUg. Considering breeding selection strategies, this study attributed information content to MU about predisposed ruminal N-utilization in Holstein–Friesians.